Determinants of the current account balance in Indonesia - Anggi Putri Kurniadi; Hasdi Aimon (Fakultas Ilmu Pendidikan UNP)
The open economic system adopted by Indonesia disrupts the current account balance. This study aims to analyze and explained the causality of the current account balance with macroeconomic variables using the VAR (Vector Autoregression) approach. The data in this study used time series from 2005 quarter 1 to 2015 quarter 4. The results showed that macroeconomic variables have no causality relationship with current account balance in Indonesia. The research recommended to the financial policy authority relates to fluctuation macroeconomic variables for a policy-making basis on the current account balance in Indonesia, because the current account balance is one of the parameters for the performance of a country's economy.